The advent of membrane-less zinc-anode aqueous batteries with lithium battery-like voltage. Issue 8 (1st June 2022) - Yadav, Gautam G.; Weiner, Meir; Upreti, Aditya; Huang, Jinchao; Lambert, Timothy N.; Arnot, David J.; Schorr, Noah B.; Bell, Nelson S.; Turney, Damon; Hawkins, Brendan; Wei, Xia; Lim, Matthew; et al.
Abstract : A 2.5 to 3.4 V Zn|MnO2 membrane-less solid-state battery accessing the 617 mA h g −1 theoretical capacity of MnO2 and its application in e-mobility is reported. This concept is made possible by a buffering layer that regulates the battery's pH. Abstract : Zinc (Zn)-anode batteries, although safe and non-flammable, are precluded from promising applications because of their low voltage (<2 V) and poor rechargeability. Here, we report the fabrication of rechargeable membrane-less Zn–anode batteries with high voltage properties (2.5 to 3.4 V) achieved through coupling cathodes and Zn–anodes in gelled concentrated acid and alkaline solutions separated by a gelled buffer interlayer containing the working ions. The concentrated gelled buffer interlayers perform dual functions of regulating the pH of the system and acting as the source and sink of the working ions. With this strategy we show low-cost membrane-less 2.5 to 3.4 V Zn–manganese dioxide (MnO2 ) batteries capable of cycling 10–100% of 617 mA h g −1 -MnO2 and 20–30% of 820 mA h g −1 -Zn and demonstrate their application in electric vehicles. This strategy is then applied to other oxide-based cathode systems like Cu2 O and V2 O5, where voltages of 2 to 3 V are obtained in membrane-less batteries.